If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 6 + -2n = 2(n + -7) Reorder the terms: 6 + 3n + -2n = 2(n + -7) Combine like terms: 3n + -2n = 1n 6 + 1n = 2(n + -7) Reorder the terms: 6 + 1n = 2(-7 + n) 6 + 1n = (-7 * 2 + n * 2) 6 + 1n = (-14 + 2n) Solving 6 + 1n = -14 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. 6 + 1n + -2n = -14 + 2n + -2n Combine like terms: 1n + -2n = -1n 6 + -1n = -14 + 2n + -2n Combine like terms: 2n + -2n = 0 6 + -1n = -14 + 0 6 + -1n = -14 Add '-6' to each side of the equation. 6 + -6 + -1n = -14 + -6 Combine like terms: 6 + -6 = 0 0 + -1n = -14 + -6 -1n = -14 + -6 Combine like terms: -14 + -6 = -20 -1n = -20 Divide each side by '-1'. n = 20 Simplifying n = 20
| 3x+.5=-6 | | 9/6=×/8 | | 3x+.6=-6 | | 4(3b-4)=8b-12 | | 0=t^2-7t+4 | | x^3-1=20 | | 4(w+2)+7w=30 | | 3x-6(x-9)= | | -2x^2-5x+1=0 | | .25=(9-2x)^2/x | | -7x-(-2x^2)= | | 10x^2-19x-6=0 | | 156=4(39+-0.5y)+2y | | 2y+5+5+17y+8= | | 42x-6-4x+20= | | 85x-4=75x | | 10/7x21/40 | | 8x=-8+16 | | 5+x^2-3+3x= | | 1/3x-1/5x | | 2z-5z=9 | | 2ab/6a | | f(x)=p^2-4p+48 | | 2.5d+7.25=2+4.25d | | 36-3x=-9 | | -7=7x+19 | | 36+24=60 | | 9p+8=16+8p | | 4/3=4 | | .2/x=2/.1 | | -1(10x+1)=59 | | 36x-3x=7x |